"Second Victim" Experiences in Obstetrics and Gynecology [339]. (May 2015) - Rivera, Enid Yvette; Lee, Colleen; Bernstein, Peter Samuel; Chazotte, Cynthia; Goffman, Dena
Abstract : OBJECTIVE: To evaluate the "second victim" experiences of health care providers at our institution to guide development of a comprehensive system to better support them. METHODS: Anonymous electronic surveys were distributed to physicians to assess knowledge of the second victim concept, stages of recovery, and to elicit personal experiences. Descriptive data are presented. RESULTS: Of 175 physicians invited, 85 (49%) completed the survey. Physicians were at various levels of training (51% trainees, 49% attendings), were primarily female (77.6%), and represented a wide variety of ages. More than one third (36%) were not aware of the concept, and only 11% were familiar with described stages of recovery. Forty-one of 85 respondents (48%) reported their most significant unanticipated adverse patient event, medical error, or patient-related injury occurred in the last 6 months (64% obstetric, 36% gynecologic). Seventy-two percent of respondents felt they were in the moving on: thriving stage; however, 28% of our health care providers remain in various other stages of recovery, including intrusive reflections, restoring personal integrity, enduring the inquisition, and moving on (surviving). The most helpful support reported by respondents was peers (66%), whereas the greatest barrier to obtaining support was available time (40%). Physicians desired the following to facilitate recovery: safe and confidential space for discussion, someone to check in on their well-being, and information about what to expect. CONCLUSION: Development of an organized support system is something that physicians at our institution feel would help after involvement in an adverse medical event. Training peers to counsel their colleagues about how to provide support after an event with frequent check-ins within a safe, confidential setting may help facilitate health care provider recovery.